Combination of feet soaking in warm water and deep breathing relaxation with classical music accompaniment to lower headaches' hypertensive patients - Dewi Nur Sukma Purqoti; Herlina Putri Rusiana; Fitri Romadonika; Elisa Oktaviana; Ernawati Ernawati (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Hypertension is a problem that is found in people in both developed and developing countries, including Indonesia. One of the symptoms of hypertension is headache and neck stiffness. Management of Hypertension consists of pharmacological and non-pharmacological therapies. Non-pharmacological therapies (foot soak in warm water and breathing therapy in classical music accompaniment) can reduce hypertension. This community service aims to health the steps of Mekar Sari citizens in hypertension cases with non-pharmacological therapies it makes comport feels. The data were obtained from the majority of residents suffering from hypertension and who had complaints of headaches and neck stiffness. The approach method is with lectures on delivery of material, then soak the feet of warm water and relaxation therapy in deep breathing with classical music accompaniment then evaluated. The results of these therapies showed the increase in knowledge about hypertension non-pharmacological therapy in Mekar Sari citizens. There was a decrease in both systolic and diastolic blood pressure and a decrease in scale after warm water foot baths and breathing therapy. Based on the service results, it is expected that this activity can be applied independently twice a week.